Pola Struktur Tematik Konten Bantuan Layanan Google Bahasa Inggris dan Versi Terjemahannya - Hafni Ayu Hapsari (PRASASTI: Journal of Linguistics, 2023)
Every language in the world has its own means to convey information that is poured through sentences. The structural patterns used also vary between languages as different thoughts of speakers of the language are also different. In the language localization industries, translation in the level of information structure from the source language into the target language must be done according to the rules that apply in the target language so that information can be conveyed precisely to the target language reader. This study aims to describe the thematic pattern in English declarative sentences found in Google's help content and their transformation in French and Indonesian using the Systemic Functional Linguistics analysis model approach developed by Halliday. The method used in this research is descriptive qualitative. The findings obtained suggest that: 1) there are no structure shifts found in thematic structures from SL to TL 1 nor from SL to TL 2, 2) there are structure shifts found in thematic structures from SL to TL 1, but no change happened from SL to TL 2, and 3) there are no structure shifts found in thematic structures from SL to TL 1, but there are changes from SL to TL 2.